Adaptive terminal sliding mode based thruster fault tolerant control for underwater vehicle in time-varying ocean currents. Issue 11 (November 2015) - Zhang, Mingjun; Liu, Xing; Yin, Baoji; Liu, Weixin
Abstract: The paper focuses on fault tolerant control for underwater vehicles in time-varying ocean environment subject to external disturbance, modeling uncertainty, and unknown thruster fault. A fault tolerant control method for underwater vehicle with thruster fault is proposed based on adaptive terminal sliding mode. Adaptive strategy is incorporated into terminal sliding mode to estimate on-line the upper bounds of the lumped uncertainties, including ocean current disturbance and modeling uncertainty, and the change of thruster distribution gain caused by thruster fault, respectively. The great advantages of the proposed method are that the prior knowledge of the lumped uncertainty is not required and it is independent of fault detection and diagnosis (FDD) module. Based on Lyapunov theory and Barbalat׳s lemma, the proposed method can accommodate thruster fault, and ensure the finite-time stability of the tracking error. Furthermore, with respect to the chattering phenomenon, a continuous switching term based on fractional power is developed in place of the discontinuous switching term. In the proposed chattering-reduction method, the continuity of switching term is achieved based on fractional power, and the gain of the proposed switching term is updated based on the exponential form of Euclidean-norm of sliding mode function. Finally, simulations and pool-experiments of underwater vehicles are carried out to demonstrate the effectiveness and feasibility of the proposed method. Highlights: An adaptive terminal sliding mode based thruster fault tolerant control is proposed. The fault information and prior knowledge of the lumped uncertainty are not required. A continuous switching term based on fractional power is developed. Simulations and pool-experiments are carried out to illustrate the efficacy.